TRANSPORTATION OPTIMIZATION IN THE DISTRIBUTION OF GASLINK CNG C-CYL PRODUCTS USING ANYLOGISTIX CASE STUDY: PT GAGAS ENERGI INDONESIA - Adji Candra Kurniawan; Figa Wafi Mustafa Mustafa; Anak Agung Ngurah Perwira Redi (INFOTECH journal, 2023)
PT Gagas Energi Indonesia is a gas subholding company, including the distribution of CNG in the form of cylinders (C-cyl). C-cyl one of the CNG development projects is packaged in a pressurized cylinder of 200-250 pcs and the volume of CNG ranges from 20 - 25 m3 with 16 - 20 kg of LPG. The problem of this research is that the route determination by the company is still done manually so that it has risks in making decisions, assumptions, causing long distances per day and causing the use of a large fleet to be able to cover all customers per day. In solving this problem, the AnyLogistix software transportation optimization model features are used which are solved with the capacited TO experiment to determine distribution routes with the characteristics of the CVRP problem. The data used are 20 location points for potential customers who have the highest demand in the industrial sector, the products used as research objects are CNG C-cyl gaslink and 125 PS Head Truck capacity. The results of the route in the AnyLogistix software for the delivery movement path January 1 2022 – January 5 2022 obtained the total route, the total distance is the same for each day with the first route starting from Pertamina Jaya Hospital, Grand Paragon Mall, PT SINAR HARAPAN PLASTIK, PT DELIDENT, Blok M Plaza, Mercure Jakarta Gatot Subroto, Karimata Taman Mini, Bhayangkara Hospital TK.I R. Said Sukanto, ABUBA Steak – Matraman with a total distance of 106.80 KM, the second route to Richesee Kalimalang, Pondok Kelapa Town Square with a total distance of 14.94 KM and the third route to PT. PIONIRBETON INDUSTRY, Dr. Mintohardjo Naval Hospital, Plataran Menteng, Mercure Jakarta Cikini, Best Western Plus Kemayoran Hotel, Whiz Prime Hotel Kelapa Gading, SANTIKA KELAPA GADING, Jakarta Harbor Hospital, Boutique Café with a total distance of 53.85 KM.